Burnout syndrome among undergraduate nursing students at a public university - Jamila Geri Tomaschewski-Barlem; Valéria Lerch Lunardi; Guilherme Lerch Lunardi; Edison Luiz Devos Barlem; Rosemary Silva da Silveira; Danielle Adriane Silveira Vidal (Universidade de São Paulo, 2014)
OBJECTIVE: to investigate the burnout syndrome and its relationship with demographic and academic variables among undergraduate nursing students at a public university in Southern Brazil.METHOD: a quantitative study with 168 students, by applying an adaptation of the Maslach Burnout Inventory - Student Survey, validated for this study. We used descriptive and variance analysis of the data analysis.RESULTS: we found that students do not have the burnout syndrome, manifesting high average scores in Emotional Exhaustion, low in Disbelief and high in Professional Effectiveness; that younger students who perform leisure activities have greater Professional Effectiveness, unlike students in early grades with no extracurricular activities; combining work and studies negatively influenced only the Professional Effectiveness factor, while the intention of giving up influenced negatively Disbelief and Professional Effectiveness factors.CONCLUSION: the situations that lead students to Emotional Exhaustion need to be recognized, considering the specificity of their study environments.